HUBUNGAN POWER OTOT LENGAN DAN BAHU TERHADAP KETEPATAN SERVIS ATAS TIM BOLA VOLI PUTRI SMA NEGERI 1 DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Yogie Nusapratama; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is when serving the SMA Negeri 1 Duri Women’s volleyball team often fails, the ball does not pass through the net, the ball out field and predictable by opponent position of the ball fall. So easily th opponent receives the top service result. The purpose of the research was t find out whether there is a muscle power relationship of the shoulder arm to the top service precision. The population in this research was the entire team of SMA Neferi 1 Duri Kecamatan Mandau Kabupaten Bengkalis women’s volleyball that amounted to 12 peoples. The sampling technique is the whole population (total sampling). The instrument perfomed in this research is test two hand medicine ballthrow, which aims to measure the muscle strength of the arms and shoulders and the top service accuracy of the samples used. After that, the data is processed with statistic to test the normality with the lilliefors test at a α0.05 significant level. Based on the results of the obtained power muscles of the arms and shoulders have a correlation to the top service precision on the SMA Negeri 1 women’s volleyball team because of Lhitung X variable = 0.1429 and Lhitung Y variable = 0.1229 where Ltabel obtaimed 0.242 (α=0.05) therefore Lhitung 0.1429 < Ltabel 0.242 on the X variable and Lhitung = 0.1229 < ltabel = 0.242 on Y variable, in other words it is concluded that the x and y data are normality distributed.Keywords : Power the musvles of the arms and shoulders, the precision of servicing the volleyball